2010
DOI: 10.4028/www.scientific.net/msf.643.131
|View full text |Cite
|
Sign up to set email alerts
|

Iron Distribution in Geopolymer with Ferromagnetic Rich Precursor

Abstract: Geompolymers and their engineering applications have attracted significant attention of the scientific community. This is due to properties such as good thermal stability and high resistance to aggressive environments. Most studies on this subject are based on traditional precursor materials such as calcined kaolinite clay (metakaolinite) and fly ash. The iron content is significant, reaching around 10% in metakaolinite, for instance. The role of iron in geopolymers still lacks systematic investigation. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…Detailed work is also ongoing to better understand the reactivity of fly ashes under alkali-activation conditions [36][37][38][39], and to valorize kaolinitic clay resources which are not of sufficient purity for use in other applications such as ceramic whitewares or coatings [40][41][42]. Common to many of these types of materials, the role of iron in alkali-activation precursors (and in the resulting binders) is beginning to be understood to some degree [19,43,44]. However, a detailed description of its reactivity and the structural implications of its inclusion in the binding gel still remain very much elusive.…”
Section: Precursorsmentioning
confidence: 99%
“…Detailed work is also ongoing to better understand the reactivity of fly ashes under alkali-activation conditions [36][37][38][39], and to valorize kaolinitic clay resources which are not of sufficient purity for use in other applications such as ceramic whitewares or coatings [40][41][42]. Common to many of these types of materials, the role of iron in alkali-activation precursors (and in the resulting binders) is beginning to be understood to some degree [19,43,44]. However, a detailed description of its reactivity and the structural implications of its inclusion in the binding gel still remain very much elusive.…”
Section: Precursorsmentioning
confidence: 99%
“…Van Deventer et al (2007) reported that reactive Fe species will most likely behave similarly to Ca 2+ , precipitating as hydroxide or oxy-hydroxide and decreasing the pH of the solution. Gomes et al (2010) used 57 Fe Mössbauer spectroscopy to determine the fate of iron during alkali activation and found that a small portion of Al 3+ could be replaced by Fe 3+ in octahedral sites. Nonetheless, Simon et al (2018) demonstrated that AAMs produced from Fe-rich slags are structurally different from "Fe-enriched" aluminosilicate geopolymers, in more than just Fe-Al substitution in tetrahedrally-coordinated sites.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the amount of CFA is increased, more aluminosilicate can participate in the reaction [5]. Furthermore, the increase of SiO2 and Al2O3, with the additional presence of Fe 3+ in the mixture, may also influence the compressive strength of the product by replacing or substituting Al 3+ by Fe 3+ in the octahedral sites of an aluminosilicate structure [39,40] . This model indicates that the proper selection of precursors needs to be determined using characterization methods.…”
Section: Regression Modelmentioning
confidence: 99%